2007
DOI: 10.1017/s1360674306002140
|View full text |Cite
|
Sign up to set email alerts
|

Emerging variation: determiner genitives and noun modifiers in English

Abstract: This article discusses the emerging variation between determiner genitives and noun modifiers in Present-day English. Based on the results of corpus analyses and previous studies I show that this variation (1) was not present in earlier English, and (2) results from the fact that determiner genitives have come to be used with nouns low in animacy while noun modifiers have come to be used with nouns high in animacy (mainly) in the course of Modern English. This semantic shift (or rather 'convergence') of geniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 13 publications
3
95
0
2
Order By: Relevance
“…London newspapers versus television screen; see Huddleston & Pullum et al 2002: 449, Rosenbach 2007. Rosenbach (2007) further distinguishes between 'classifier' versus 'determiner' functions for premodifying nouns that are complements. While it is possible to cite clear-cut examples for these distinctions, many natural occurrences of NN sequences are intermediate and difficult to classify.…”
Section: Nouns As Nominal Premodifiersmentioning
confidence: 99%
“…London newspapers versus television screen; see Huddleston & Pullum et al 2002: 449, Rosenbach 2007. Rosenbach (2007) further distinguishes between 'classifier' versus 'determiner' functions for premodifying nouns that are complements. While it is possible to cite clear-cut examples for these distinctions, many natural occurrences of NN sequences are intermediate and difficult to classify.…”
Section: Nouns As Nominal Premodifiersmentioning
confidence: 99%
“…In early Modern English s-genitives were still basically restricted to animate nouns (Rosenbach and Vezzosi, 2000), it is only in the course of Modern English that the s-genitive also spreads to inanimate nouns (cf. Rosenbach, 2002Rosenbach, , 2007a. In the early Modern English period we can already find a few 'outliers', i.e.…”
Section: Background: the Role Of Animacy In English Genitive Variationmentioning
confidence: 99%
“…Recently, however, Rosenbach (2007a) has shown that this variation is also strongly determined by animacy in that human dependents prefer the s-genitive while inanimate dependents are preferably realized as noun modifiers. That is, Mair's dinner party is more likely than the Mair dinner party, and the hotel lobby is more frequent than the hotel's lobby.…”
Section: Determiner S-genitives Versus Noun Modifiersmentioning
confidence: 99%
See 2 more Smart Citations